Interpersonal Strategies in E-Complaint Refusals: Textbook Advice Versus Actual Situated Practice. Issue 3 (September 2020) - Decock, Sofie; De Clerck, Bernard; Van Herck, Rebecca
This article reports on the representation and operationalization of interpersonal attention in complaint management by comparing business textbooks, service recovery research, and situated practice. While textbooks commonly recommend the use of interpersonal strategies when writing complaint refusals, service recovery research points toward contextual differences in this regard. We use an authentic sample of complaint refusals from an intercultural business-to-business setting to show that the decontextualized recommendations in textbooks are not always applied in actual practice and that this lack of interpersonal attention need not be problematic.